Learning Interconnectedness: Internationalisation through Engagement with One Another. (January 2014) - Spiro, Jane; Henderson, Juliet
Abstract This study explores the view that student engagement with one another is critical in the internationalisation mission. Although universities make powerful claims regarding their international mission and goals, international and home students report isolation from one another. Whilst the literature is rich in its discussion of policy, institutional meanings and student voice, it offers us less insight into how internationalisation might be translated into classroom practice. The study shares examples of four small‐scale projects in which students engage with one another across cultural boundaries in practical and problem‐solving activities. What students value in the approach is explored through interview, focus groups, diary reflections and evaluations. The findings suggest that students who engage with one another across cultural boundaries in practical and pragmatic ways, experience significant change in their assumptions and feel more readily able to view themselves as members of an international learning community. The study arrives at the view that the evolution of communities of practice, based on principles of equality, shared goals and guided reciprocity can bring international and home students together in a process of effective mutual learning that meets some of the goals of the internationalisation.